2020
DOI: 10.1097/md.0000000000022667
|View full text |Cite
|
Sign up to set email alerts
|

Is the proximal adductor canal block a better choice than the distal adductor canal block for primary total knee arthroplasty?

Abstract: Background: Total knee arthroplasty is accompanied by moderate to severe postoperative pain. Postoperative pain hampers the functional recovery and lowers patient satisfaction with the surgery. Recently, the adductor canal block (ACB) has been widely used in total knee arthroplasty. However, there is no definite answer as to the location of a continuous block within the ACBs. Method: Randomized controlled trials about relevant studies were searched in PubMed (1996 to Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The conclusions of this review were consistent with those of a previously published meta‐analysis 43 . Specifically, both reviews revealed no significant between‐group differences in total opioid consumption, catheter insertion time, or block success rate.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The conclusions of this review were consistent with those of a previously published meta‐analysis 43 . Specifically, both reviews revealed no significant between‐group differences in total opioid consumption, catheter insertion time, or block success rate.…”
Section: Discussionsupporting
confidence: 88%
“…The conclusions of this review were consistent with those of a previously published meta‐analysis. 43 Specifically, both reviews revealed no significant between‐group differences in total opioid consumption, catheter insertion time, or block success rate. However, our review found that proximal ACB could provide less pain during rest at 2 h and 24 h after surgery, which contrasts with their results.…”
Section: Discussionmentioning
confidence: 93%
“…Another important factor to consider is relative block success rates among providers. For TKA, for example, while the adductor canal block may have >90% success rates in experienced hands,36 those less experienced may have lower success rates, reducing their confidence in RA for the surgery. Providers less confident in RA-based techniques may be less inclined to offer RA for common surgeries, starkly different from centers that may have standardized RA delivery protocols in place irrespective of provider preferences.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 However, a recent meta-analysis of proximal versus distal sites of injection found no difference in opioid use or in mean or maximum pain scores between the two approaches. 14 Perhaps this reflects what some anatomic 8,15 and clinical 15 studies have shown: injectate has the capacity to flow within the subsartorial canal, and even traverse the boundaries between the distal FT, the anatomic AC, and the popliteal fossa.…”
mentioning
confidence: 86%